Perbedaan Kinerja Keuangan Dan Relevansi Nilai Sebelum Dan Sesudah Penerapan Konvergensi Psak Ke Ifrs Studi Pada Perusahaan Non Keuangan Yang Terdaftar Di Bursa Efek Indonesia - Raden Rosiyana Dewi; Reslini Femila (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2012)
The purpose of this study to examine whether there are differences in the increase or decrease the impact of the third application of IFRS adoption of SFAS IA1 has issued the applicable date of January 1, 2008, the PSAK 13 on Investment Property, PSAK 16 on Fixed Assets, and PSAK 30 of the Lease, the companies are already applying IAS adoption. Tests conducted on the influence of the application of the convegence offinancial performance, as seen from the company's size, activity, Solvency, Growth, Profitability, and Investment Company performance. And Testing the influence of convergence on the value relevance of financial information of the relevance value of the company seen net income and equity book value to price shares of the company. Thesis inconnection with GAAP to IFRS convergence series launched by IAI in 2008. The research was carried out on non-financial companies listed on the Stock Exchange Indonesia (BEI) and using secondary data derived from the financial report and the Indonesian Capital Market Directory (ICMD) in the period 2006-2010. Authors obtain the 36 companies selected as the study sample.